SMAD3 Host and Tumor Profiling to Identify Locally Advanced Rectal Cancer Patients at High Risk of Poor Response to Neoadjuvant Chemoradiotherapy - De Mattia, Elena; Canzonieri, Vincenzo; Polesel, Jerry; Mezzalira, Silvia; Dalle Fratte, Chiara; Dreussi, Eva; Roncato, Rossana; Bignucolo, Alessia; Innocente, Roberto; Belluco, Claudio; Pucciarelli, Salvatore; De Paoli, Antonino; et al. (Frontiers in Pharmacology, 2021)
Identifying patients at risk of poor response to neoadjuvant chemoradiotherapy (nCRT) is an emerging clinical need in locally advanced rectal cancer (LARC). SMAD3 is a key player in the chemoradio-resistance phenotype and its expression is both constitutive and locally induced. The aim was to investigate both host (genetic polymorphisms) and tumor SMAD3 profiling to predict response to nCRT. In a group of 76 LARC patients, SMAD3 and phosphorylated-SMAD3 expression was assessed by immunohistochemistry in preoperative tumor tissue. In an expanded study group (n = 378), a set of SMAD3 polymorphisms (rs35874463, rs1065080, rs1061427, rs17228212, rs744910, and rs745103) was analyzed. Association with tumor regression grade (TRG) and patient prognosis (progression-free survival [PFS] and overall survival [OS]) was assessed. Patients with high tumor expression of SMAD3 had a significantly increased risk of poor response (TRG≥2) [cellularity >55% (OR:10.36, p = 0.0004), or moderate/high intensity (OR:5.20, p = 0.0038), or an H-score≥1 (OR:9.84, p = 0.0004)]. Patients carrying the variant SMAD3 rs745103-G allele had a poorer response (OR:0.48, p = 0.0093), a longer OS (HR:0.65, p = 0.0307), and a trend for longer PFS (HR:0.75, p = 0.0944). Patients who carried both high SMAD3 tumor expression and the wild-type rs745103-A allele had an extremely high risk of not achieving a complete response (OR:13.45, p = 0.0005). Host and tumor SMAD3 status might be considered to improve risk stratification of LARC patients to facilitate selection for alternative personalized neoadjuvant strategies including intensified regimens.